Towards a Methodology for Rethinking Modernity: Between Imagined, Realized, and Lived Space (EAAE Annual Conference Proceedings, 2019)
There is a global aspiration for continuous improvements of teaching curricula and teaching models in the field of architectural design, especially in response to the changing context of architectural education. New research areas and thematic frameworks within it are being continuously re-introduced and becoming more process and problem-oriented. Traditional teaching approaches and established programs thus require the development of extended forms of the teaching process and learning that empowers students to develop their competencies and skills further. The basic study program at the University of Belgrade — Faculty of Architecture covers various curricula and aspects of reflection that are autonomously examined from the architectural, urban and technological level. Especially, the teaching curricula for studies of modernity, that is a thematic focus of the paper, are established within different study programs and levels of study, which very often disables logical chronology of learning and an integral consideration of the phenomenology of modernity.
Keywords: workshop; architectural design; architectural programming; urban studies; phenomenology of modernity